The Role of Enterprise Resource Planning in Improving Data Integration and Managerial Decision Making - Ayu Hasnining; Mushaf (Program Studi Teknik Komputer, 2025)
This study aims to examine the role of Enterprise Resource Planning (ERP) in improving the integration of operational data and managerial decisions at IFAH Group. The main problem raised is the non-optimal utilization of ERP as a strategic tool in supporting data-based decision making. Using a quantitative approach with a correlational design, 50 respondents were selected through purposive sampling. Data were collected through a Likert-scale closed questionnaire and analyzed with multiple linear regression using SPSS. Results show ERP has a significant effect on data integration and managerial decisions (R² = 0.574; p < 0.001), with data integration as a mediator. This study confirms the importance of ERP in the digital transformation of organizations. However, this research is limited to one case study and user perceptions, so further research with a multi-method approach or in different industry contexts is recommended